Currency blocs in the 21st century - Christoph Fischer (Bank of Finland, Institute for Economies in Transition (BOFIT), 2012)
Based on a classification of countries and territories according to their regime and anchor currency choice, the study considers the two major currency blocs of the present world. A nested logit regression suggests that long-term structural economic variables determine a given country's currency bloc affiliation. The dollar bloc differs from the euro bloc in that there exists a group of countries that peg temporarily to the US dollar without having close economic affinities with the bloc. The estimated parameters are consistent with an additive random utility model interpretation. A currency bloc equilibrium in the spirit of Alesina and Barro (2002) is derived empirically.
URN:NBN:fi:bof-201408071957
Keywords: F02; F31; F33; E42; C25; 330; anchor currency choice; nested logit; exchange rate regime classification; additive random utility model; currency bloc equilibrium